Advantages of oral collagen supplementation. Review of the literature - Kotowicz, Zuzanna; Pich-Czekierda, Aleksandra; Proszowska, Patrycja; Orzeł, Adrianna; Sieniawska, Daria; Madoń, Magda; Sieniawska, Julia (Journal of Education, Health and Sport, 2024)
Introduction Collagen is a protein that has found widespread use both as an ingredient in cosmetics applied externally and as an oral supplement. This substance is obtained from a number of animal sources, including bovine tissues, as well as marine fish. The characteristic properties of collagen peptides, such as scientifically proven anti-inflammatory effects, activation of fibroblast skin cells, stimulation of synovial cells to produce hyaluronic acid, and much more make this type of supplement promising in improving the body's general condition and in alleviating the symptoms of many ailments. Numerous scientific studies have shown that supplementation with hydrolyzed collagen has a beneficial effect on both the overall condition of the skin by improving its elasticity, hydration level, and positive action on its protective barrier and on the musculoskeletal system, where, when combined with appropriately selected physical activity, it can help to reduce pain associated with conditions such as osteoarthritis and even increase the range of movement in the joints. Easy availability, user-friendly forms of administration, such as powders or ready-to-drink liquid formulations, and a low incidence of side effects make this supplementation highly beneficial for users. Aim of the study This study aims to discuss the known processes and review the evidence supporting the beneficial effects of hydrolyzed collagen supplementation on the human skin and musculoskeletal system. Material and method This article presents the current state of knowledge about the benefits of oral collagen peptide supplementation in various scientific articles. Publications describing the mechanisms of action and the effects of collagen supplementation on skin conditions and the musculoskeletal system, including recent reports in this field, were reviewed using the PubMed platform. The search included the keywords ‘collagen’, ‘collagen supplementation’, ‘nutritional supplement’, ‘recovery’